Zygotic degradation of two maternal Cdc25 mRNAs terminates Drosophila's early cell cycle program. - Edgar, B.A.; Datar, S.A. (Genes & Development, 1996)
In Drosophila embryos the maternal/zygotic transition (MZT) in cell cycle control normally follows mitosis 13. Here we show that this transition requires degradation of two maternal mRNAs, string and twine, which encode Cdc25 phosphatases. Although twine is essential for meiosis and string is essential for most mitotic cycles, the two genes have mutually complementing, overlapping functions in the female germ line and the early embryo. Deletion of both gene products from the female germ line arrests germ-line development. Reducing the maternal dose of both products can lower the number of early embryonic mitoses to 12, whereas increasing maternal Cdc25(twine) can increase the number of early mitoses to 14. Blocking the activation of zygotic transcription stabilizes maternal string and twine mRNAs and also allows an extra maternal mitosis, which is Cdc25 dependent. We propose that Drosophila's MZT comprises a chain reaction in which (1) proliferating nuclei deplete factors (probably mitotic cyclins) required for cell cycle progression; (2) this depletion causes the elongation of interphases and allows zygotic transcription; (3) new gene products accumulate that promote degradation of maternal mRNAs, including string and twine; and (4) consequent loss of Cdc25 phosphatase activity allows inhibitory phosphorylation of Cdc2 by Dwee1 kinase, effecting G2 arrest. Unlike timing or counting mechanisms, this mechanism can compensate for losses or additions of nuclei by altering the timing and number of the maternal cycles and thus will always generate the correct cell density at the MZT.